2019
DOI: 10.1177/0033294119850480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Color on Emotion Recognition Is Not Bidirectional: An Investigation of the Association Between Color and Emotion Using a Stroop-Like Task

Abstract: The association between color and emotion has been shown, with red facilitating recognition of anger and green facilitating recognition of happiness. However, it has been unclear if emotional stimulus conversely facilitates and/or inhibits recognition of such colors. This study used a Stroop-like task, which required participants to ignore facial expressions and recognize color, in order to investigate the influence of emotion on recognition of color. In addition, this study investigated the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
4
20
4
Order By: Relevance
“…The analysis of correct response rate found no significant effects of background colors or the emotions in the facial stimuli, perhaps due to the ceiling effect. The analysis of response time, on the other hand, showed that judgment of a happy face was faster than judgment of a sad face against a yellow background, consistent with the previous finding (Ikeda, 2020). However, contrary to our hypothesis, judgment of happy and sad faces was not affected by a blue or gray background.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The analysis of correct response rate found no significant effects of background colors or the emotions in the facial stimuli, perhaps due to the ceiling effect. The analysis of response time, on the other hand, showed that judgment of a happy face was faster than judgment of a sad face against a yellow background, consistent with the previous finding (Ikeda, 2020). However, contrary to our hypothesis, judgment of happy and sad faces was not affected by a blue or gray background.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of social cognition, it is important for humans to understand others' emotional states. Facial expressions function as one of the most effective cues when people recognize others' emotions (Collignon et al, 2008;Ikeda, 2020;Massaro & Egan, 1996;Van den Stock et al, 2007). Humans also utilize other resources, including emotional contexts (Barratt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such modulatory effects of the green stop-cues on ensuing behavior has not been reported in humans yet. The proposed models of color-hierarchy in driving avoidance-approach behavior in humans (Elliot, 2015;Mehta & Zhu, 2009) have been mainly focused on the red and blue colors, however in humans green color is associated with positive emotions and feelings (Dzulkifli & Mustafar, 2013;Ikeda, 2019) and creative behavior (Lichtenfeld et al, 2012). Further studies in humans, comparing red, green and blue in the context of the same task would be necessary to reveal the order of color-hierarchy in each task and its correspondence with that in monkeys.…”
Section: Response Inhibitionmentioning
confidence: 99%